Nidificação colonial de Butorides striata (Linnaeus, 1758) (Ciconiiformes: Ardeidae) em área alagável no município de Porto Esperidião, Mato Grosso - Almeida, Sara Miranda; Evangelista, Mahal Massavi; Silva, Evandson José dos Anjos (Papéis Avulsos de Zoologia, 2012)
Butorides striata (Striated Heron) breeds during the rainy season in the Neotropics. This species generally breeds solitary or in small groups and, exceptionally, in colonies of 300 to 500 pairs. Here we report nesting site, nest type, egg characteristics, incubation period, nestling period, nest failures, reproductive success and nesting period recorded in Porto Esperidião county, Mato Grosso State, Brazil. Search for the nests started on July 2009 and ended on May 2010 and one hundred and fifteen active nests were found. The first active nest was found in early January 2010 and the last remained active until late April 2010. The nest is a platform of dry and thin twigs measuring around 20-30cm each. The incubation time was of 24.88 days (max=27, min=24, SD=1.07, n=102), and the fledgling time was of 20.83 days (max=23, min=20, SD=1.16, n=17). Three eggs were found in 60% of nests found (n=102). According to the Mayfield protocol the breeding success was 16.43%.